Constitutional Rules and Agricultural Policy Outcomes - Olper, Alessandro (World Bank, Washington, DC, 2017)
This paper deals with the effect of constitutional rules on agricultural policy outcomes in a panel of observations for more than 70 developing and developed countries in the 1955-2005 period. Testable hypotheses are drawn from recent developments in the comparative politics literature that see political institutions as key elements in shaping public policies. Using differences-in-differences regressions we find a positive effect of a transition into democracy on agricultural protection. However, this average effect masks substantial heterogeneities across different forms of democracy. Indeed, what matters are transitions to proportional democracies, as well as to permanent democracies. Moreover, while the author does not detect significant differences across alternative forms of government (presidential versus parliamentary systems), there is some evidence that the effect of proportional election is exacerbated under parliamentary regimes, and diminished under presidential ones.